2022
DOI: 10.1101/2022.05.21.492926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of metabolism and regulation reveals rapid adaptability to growth on non-native substrates

Abstract: Engineering synthetic heterotrophy (i.e., growth on non-native substrates) is key to efficient bio-based valorization of various renewable (e.g., lignocellulosic biomass) and waste (e.g., plastics) substrates. Among these, engineering hemicellulosic pentose utilization has been well-explored in Saccharomyces cerevisiae (yeast) over several decades but genetic factors that constrain maximum growth rate remain elusive. Through a systematic analysis (flux balancing, directed evolution, functional genomics, and ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…While all three approaches reached similar nal cell concentrations on each of the three substrates, the ∆GAL80 condition took roughly twice the time to do so compared with Gal3p Syn4.1 and Gal3p MC (>30 h vs. ~18 h) suggesting that de-regulation of the regulon results in reduced tness relative to strains in which the native regulatory organization is maintained. As sucrose and glucose are both capable of exerting repression on the GAL regulon 19 , subculturing all three strains from these two native substrates into complex (YP) media containing the non-native substrate xylose should therefore result in growth-coupled expression of xylose catabolic genes and rapid growth. Upon subculturing from sucrose, we observed that all three approaches enabled growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While all three approaches reached similar nal cell concentrations on each of the three substrates, the ∆GAL80 condition took roughly twice the time to do so compared with Gal3p Syn4.1 and Gal3p MC (>30 h vs. ~18 h) suggesting that de-regulation of the regulon results in reduced tness relative to strains in which the native regulatory organization is maintained. As sucrose and glucose are both capable of exerting repression on the GAL regulon 19 , subculturing all three strains from these two native substrates into complex (YP) media containing the non-native substrate xylose should therefore result in growth-coupled expression of xylose catabolic genes and rapid growth. Upon subculturing from sucrose, we observed that all three approaches enabled growth.…”
Section: Resultsmentioning
confidence: 99%
“…By placing heterologous genes for either xylose or arabinose catabolism under the control of GAL-responsive (Leloir pathway) promoters, the GAL regulon could be adapted for growth on these non-native substrates. Upon comparing this regulon-coordinated (REG) approach to growth with simple constitutive overexpression of the same catabolic genes, which we term a constitutive (CONS) approach, we found that our semi-synthetic regulon yielded superior growth rates on both xylose (µ = 0.24 h -1 vs. 0.11 h -1 ) and arabinose (µ = 0.27 h -1 vs. 0.06 h -1 ), respectively with minimal metabolic engineering 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar range of growth rates was observed for the xylose constructs (0.20 − 0.21 h -1 ) but the substantially reduced final cell density of two of the arrangements (ϕ-XK-XI and XK-ϕ-XI) indicates that there can be fitness consequences to expression imbalances. As no clearly superior combination could be identified to the initial arabinose and xylose designs, we decided to re-test a Consolidated approach to co-utilization on 1 % of each substrate (Figure 6E) using designs (ABD for arabinose, XI-ϕ-XK for xylose) identified as optimal in a related investigation by our lab into efficient pentose assimilation 19 .…”
Section: Gal3p MC Enables Rapid and Complete Co-utilization Of Multip...mentioning
confidence: 99%
“…Upon comparing this regulon-coordinated (REG) approach to growth with simple constitutive overexpression of the same catabolic genes, which we term a constitutive (CONS) approach, we found that our semi-synthetic regulon yielded superior growth rates on both xylose (µ = 0.24 h -1 vs. 0.11 h -1 ) and arabinose (µ = 0.27 h -1 vs. 0.06 h -1 ), respectively with minimal metabolic engineering 19 . Significantly, a transcriptomic comparison showed relative upregulation of genes associated with cell division and mitochondrial biogenesis in the REG strain while the CONS strain showed upregulation of stress response and starvation-associated genes 18 .…”
Section: Introductionmentioning
confidence: 99%